Validation of an instrument to identify actions for screening and detection of breast cancer. - Vilanova Marques, Carla Andréia; Níglio de Figueiredo, Elisabeth; Rivero de Gutiérrez, Maria Gaby (Acta Paulista de Enfermagem, 2015)
Objective: To develop and validate a questionnaire to identify the actions performed in screening and detection of breast cancer in Brazil, and to determine its applicability. Methods: A methodological study, with the participation of three experts and a pilot test with 85 users of four primary health care services, with a descriptive data analysis. Results: Of the 132 questions formulated and organized in the structure and process dimensions undergoing validation, there was a 96.7% and 78.8% agreement of the evaluators in the first and second rounds, respectively. Most of the questions were understood by those involved in the investigation. The absence of the medical record resulted in the exclusion of 40 questions, resulting in 83 questions in the final version. Conclusion: The content of the instrument was adequate to evaluate actions to control breast cancer in primary care. The pilot test confirmed its applicability, and the need for improvements in documenting information.